Government Expenditure and Its Effect on National Income and Employment in India - Kumar Sinha, Jitendra (Journal of Advanced Research in Economics and Business Management, 2022)
This study includes the analysis of the effect of government expenditure on the growth of employment and national income in India. This study used the Dynamic panel models. Pooled Mean Group (PMG) estimator was found to be the appropriate choice as per the Hausman test. The analysis shows that the impact of an increase in government expenses on national income and employment is more as compared to that of a decrease in government spending. Hence the government plays a major role in increasing national income and employment opportunities.The relative share of expenditure in the Defence services sector has been higher, but this sector has not shown any causal linkage with income from any of the sectors, thereby indicating that expenditure incurred on such activities has been less productive. Further, substantial expenditure on the Education sector has failed to generate income demanding adequate steps to be taken so that such activities could indeed lead to human capital formation, known to be a prerequisite for the development of an economy. The study recommends proper use of the resources of government and powerful tools and policies that can help in achieving an equitable distribution of income and wealth.